Pengembangan YouTube Desa sebagai Media Promosi Potensi Desa Klatakan - Ida Fitriana Ambarsari; Yuni Maulida; Fathor Rosit; Fathol Latif; Ahmad Karomi (Abdimas Universal, 2024)
The use of YouTube as a video sharing platform has become a global phenomenon, and its potential is not only limited to the surrounding environment, but can also be applied at the village level, of course, in Klatakan Villages, Situbondo. The YouTube application already exists on local people’s smartphones. This is characterized by people frequently accessing YouTube in their daily lives, depending on the amount of data quota, or using free wifi networks in various places. This article discusses the innovative concept of developing YouTube as a promotional media to increase the visibility and potential of the local economy in the village by focusing on the benefits for village tourism, developing local products, and empowering the community in Klatakan Village. This approach can be a strategic tool in connecting Klatakan Village with the digital world. In this discussion, we detail 15 references that support this idea, including literature on online interactions, social media marketing, and guerilla marketing strategies. YouTube village development is not just about showcasing the village visually, but also about creating community involvement and sustainable economic opportunities. Through this concept, it is hoped that Klatakan Village can take advantage of the advantages of digital technology to elevate their local potential and increase connectivity with the global community.